A Comparison of Heart Rate in Normal Physical Activity vs. Immersive Virtual Reality Exergames - Varela-Aldás, José (2020)
Regular physical exercise helps to maintain a good physical condition besides a healthy life, but the new working conditions and the needs of modern man makes hard to practice a sport, so a new tendency to practice sports periodically are the exergames, based in the immersive virtual reality, to allow new possibilities of games with different levels of physical activity. This work focuses on the comparison of the heart rate generated through normal physical activity compared with the obtained through by an immersive exergame, the physical activity employed was table tennis and the application was implement in the Gear VR with controller. The application was develop in Unity, using a mobile device compatible with virtual reality, and a Mi band 3 sensor, which acquires heart rate data. Finally, results indicated a decrease in heart rate in the case of the exergames, demonstrating that this technology does not substitute conventional physical activity in spite of the benefits, although the usability test was satisfactory. © Springer Nature Switzerland AG 2020.